ASURANSI KERANGKA KAPAL PERIKANAN SEBAGAI STRATEGI MANAJEMEN RISIKO (STUDI KASUS: PERUSAHAAN UMUM PERIKANAN INDONESIA) - Bunga Mega Aprilia; Fis Purwangka; Akhmad Solihin (Jurnal Teknologi Perikanan dan Kelautan, 2019)
Fishing vessel operational activities have a high risk of accidents, those causing losses to the ship owner. The government has required fishing vessel frame insurance to the ship owner through a mandatory circular for the removal of the ship's framework and/or compensation protection. This study aims to describe the rules of ship insurance in Indonesia with a normative juridical law. Next, identify fishing vessel requirements for submission of insurance with a descriptive analysis and find out the gap in the implementation of fishing vessel frame insurance at Perum Perindo and provide recommendations for implementation with gap analysis. The results of this study, it is known that the rules regarding fishing vessel frame insurance contained in Law No. 17/2008 (Article 203), PP No. 5/2010 (Article 119), and PermenHub No. 71/2013 (Article 18). Required insurance requirements are grosse akta, surat ukur, and pas besar. The implementation gap for fishing vessel frame insurance at Perum Perindo is 40%. Recommendations for implementing insurance are suggested that the ship owner completes the document of ownership of the ship which is the insurance requirement and the preparation of funds to pay premiums to third parties.